A construção de conceitos nas peças publicitárias sobre automóveis: Um estudo sobre a interferência cultural na geração de mensagens - Farias, Vânia Penafieri de (2006)
The study is about the examination of the semiotics building of the animal aspect and the superdimension of the time and the space, in the automobile messages on the printed advertising pieces. How the advertinsing is intrinsically related to cultural habits and behaviour tendencies, through the study of better understanding of the signal relations which are formed by cultural interferences. The research has considered the hypotheses of the landscapes created on the advertising pieces take the privilage, from one side, the individuality as a generator concept of the unity of the automobile, on the other hand, the plurality with the idea of achieveness of exhibition. The other hypothesis is about the idea of spacial escape idea versus the simbolic run away of the urban daily life. The paper was structered in a way to make possible: identification of the present diversities in the corpus, thought about the automobile representations in the post-modern society and dialogical possibilities, base don Mikhail Bakhtin concept, among many structures existing on the advertising pieces